Elite-level cooperation and opposition dynamics during defensive transitions: Using computer vision data to estimate the pass and dribbling progression conceded - Freitas, R.; Lopes, R. J.; Sarajärvi, J.; Volossovitch, A. (International Journal of Sports Science & Coaching, 2025)
This study examined how cooperation and opposition dynamics influenced ball progression during open-play defensive transitions in football. Ninety-four matches from the top three teams in the Portuguese First League (2022/23) were examined, focusing on episodes beginning in the offensive midfield of teams that lost ball possession, with a balanced scoreboard, and where possession was not regained. A five-second time criterion was used to define the endpoint of each transition. Thirty-six predictor variables, related to interpersonal angles, distances, and Voronoi diagrams were analysed using three Linear Mixed Models, based on each episode's type of progression (dribbling, passing, or mixed). Results indicated that a greater average distance between the first defender and the ball reduced progression through passing (ß = -0.15; CI = -0.24, -0.06), while greater variations in distances between the first two defenders and the ball generally hindered progression. Larger Voronoi areas for the third defender correlated with greater opponent spatial advances (ß = 0.19; CI = 0.11, 0.27), likely reflecting attacking success rather than defensive failure. Unexpectedly, higher spatial dominance around the first defender was associated with reduced defensive success (ß = 0.15; CI = 0.08, 0.22 and, ß = 0.10; CI = 0.03, 0.18), possibly due to lack of compactness or an episode's selection bias. Wider angles between defenders and their own goal positively correlated with all types of progression, emphasising the importance of maintaining defensive alignment. Overall, these findings reveal how specific defensive patterns near the ball can be used to obstruct opponents` progression during defensive transitions.